ال َع ْو ُد في الجریمة ّ دراسة مقارنة بین الش ْ ریعة الإس ُ لامیة والقانون الجزائري - خلایفة, یاسین (University of eloued جامعة الوادي, 2015)
یهدف هذا البحث إلى معرفة ظاهرة العود في الجریمة من حیث أسبابها وشروطها وطرق إثباتها والآثار الناتجة عنها، كما یهدف الى إیضاح أسباب ظاهرة العود في الجریمة والتي تشمل الإنسان والبیئة والنظام والعقوبة، والوقوف على آثار هذه الظاهرة المتعلقة بعقوبة المجرم العائد وطریقة تنفیذها وملائمة تشدیدها وعلاقتها بذات المجرم. كما یهدف إلى طرح الحلول المناسبة لمعالجة أسباب هذه الظاهرة للقضاء علیها لكونها تمثل مشكلة مستعصیة أمام العاملین في مجال مكافحة الجریمة. هذا ونؤكد ن كانت تمث ٕ على أن ظاهرة العود في الجریمة وا ل عائقاً كبیراً أمام المختصین في مكافحة الجریمة إلا أن الحلول المقترحة للقضاء علیها في متناول الباحثین وفي مقدور المختصین بدلیل أن السوابق والتجارب الماضیة التي تؤكد قدرة الإنسان في إصلاح نفسه وغیره بقوة الأنظمة. This research aims to know the phenomenon of recidivism offence in terms of the causes, conditions and modes of proof and the resulting effects, it also aims to clarify the causes of the phenomenon of recidivism in organized crime, including human and environment, order and punishment, and the effects of this phenomenon on the criminal punishment return method implementation and appropriate emphasis and their relationship with the offender. It also aims to offer appropriate solutions to address the causes of this phenomenon to eliminate them as a problem before working in the fight against crime. This and emphasize that the phenomenon of recidivism in the crime and that they represent a significant obstacle to the specialists in the fight against organized crime, but that the solutions proposed to eliminate it accessible to researchers and specialists can guide the precedents and past experiences that human capacity to reform itself and other power systems
شريعة وقانون
Keywords: القانون الجزائري/الجريمة/العود; Algerian Law/Crime/